Kyrgyz in eastern sources (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this article, the eastern historian Rashid ad-Din reports the following about the “Kyrgyz tribe” in the “Collection of Chronicles”: “The Kyrgyz and Kem-Kemdzhiut” are two neighboring peoples, together they form one power (state), “Si-shi- Izide» (Xlll k) when talking about the Kirghiz, Ertysh and Altai territories is described as two. According to “Yuan-Shi”, the region “Kian-Kian Zhou” is located in the southeast of the Kyrgyz country, at the same time “Kem”, i.e. It is located west of the Yenisei River. From this period, as in the “Tang” period before the formation of the Great Kyrgyz Khaganate (state), it is possible to obtain information about the lands that belonged to the Kyrgyz tribes, the mountains and waters where they lived, and the location of the tribes. bordering them and even living under the rule of the Kyrgyz.
Keywords: Kyrgyz, Central Asia, East, Naiman, Yenisei, Kaganate, Altai